28 AGING EFFECTS ON THE PROLIFERATION AND DIFFERENTIATION CAPACITY OF ADIPOSE STEM CELLS. Issue 1 (1st January 2007) - Arboleda, V. A.; Kun, S.; Lopez, V.; Zhang, R.; Rodríguez, L. V.
Abstract : Purpose: The therapeutic potential of stem cells is enormous. Cell-based therapies of diseases affecting the lower urinary tract using stem cells appear promising. Most of these diseases, such as incontinence, affect predominantly the elderly, yet most research of adult-derived stem cells has been conducted in cells from young individuals. Thus, little is known about individual variations within characterized stem cell lineages and the multipotential capacity of these cells in the elderly. We sought to compare the proliferative and differentiation capacities of different sources of adipose stem cells (ASCs) derived from young and elderly rats and evaluate the effects of senescence on these cells. Methods: Fat was harvested from the inguinal/abdominal, retroperitoneal, and gonadal regions of 3-month and 24-month female Fischer 344 rats and processed to obtain ASCs. P1 passage cells were plated for proliferation and cells were counted daily by hemocytometer. P1 passage cells were differentiated in specific media as previously described. Osteogenic differentiation was assessed quantitatively and qualitatively for Ca 2+ and alkaline phosphatase. Smooth muscle differentiation was assessed by the presence of smooth muscle specific markers by flow cytometry and immunohistochemistry. Senescence of the cells was measured by telomerase activity. Results: Gonadal and retroperitoneal ASCs from older rats have significantly decreased proliferation and differentiation into osteoblastic and leiomyogenic than ASCs from younger animals. In contrast, inguinal/abdominal ASCs from aged rats have an increased proliferation, clonogenic capacity, and osteoblastic differentiation capacity compared with younger rats. Additionally, inguinal ASCs maintain their ability to differentiate into smooth muscle as they age and show an increase in the expression of actin, calponin, and MHC. Aged ASCs from all regions have increased telomerase activity compared with younger rats, with the greatest increase observed in the inguinal/abdominal region. Conclusions: There are regional differences in the effect of aging in ASC obtained from different fat depots. Senescence of the cells may account in part for decreases in proliferation and differentiation capacity of ASC obtained from gonadal and retroperitoneal regions. The aged inguinal/abdominal fat maintains a population of ASC with high levels of telomerase activity that maintain normal proliferation and differentiation capacity. This telomerase up-regulation is typical of stem cells and is maintained in the aged animals. This, combined with the ease of access of adipose tissue in this region, makes it an ideal source of stem cells for cell-based therapies in the elderly population.